STRATEGI HUMAS PANTI ASUHAN YAYASAN AL AKBAR PEKANBARU DALAM MENGATASI COVID-19 - Rosmala; Susi Artuti Erda Dewi (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
The background of this research stems from the conditions that have occurred at the Al Akbar foundation orphanage since the Covid-19 pandemic that hit the last two years had an impact on the Social Welfare Institution in Pekanbaru so that the donors who initially regularly helped slowly stopped donating. This study aims to find out how the Al Akbar Foundation's public relations strategy in overcoming the conditions caused by Covid-1. As a public relations orphanage, operational institutions certainly need a good communication strategy between parties in overcoming the effects of Covid-19. The type of research used in this study is a qualitative research with a descriptive approach. The methodology used includes data collection, data reduction, data presentation, and depiction. From the results of the study, it is known that the strategy implemented by public relations in overcoming the conditions due to covid 19 can run well, because it applies the first four strategies of the operational strategy approach; both approaches to strategy responsibility; the third is a persuasive and educative strategic approach, and the last is a cooperative strategy approach. Basically the strategy can be implemented by public relations but needs to be improved on a cooperative strategy approach. Due to the presence of covid-19 as donors stopped providing assistance, but problems can be overcome with the responsibility of public relations to maintain harmonious relationships resulting in new collaborations with new prospective donors for a better future at the Al Akbar orphanage.